The relation between privacy protection and risk attitudes, with a new experimental method to elicit the implicit monetary value of privacy - Alisa Frik; Alexia Gaudeul (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
We investigate the decision of experimental subjects to incur the risk of revealing personal private information to other participants. We do so by using a novel method to generate personal information that reliably induces privacy concerns in the laboratory. We show that individual decisions to incur privacy risk are correlated with decisions to incur monetary risk. We find that partially depriving subjects of control over the revelation of their personal information does not lead them to lose interest in protecting it. We also find that making subjects think of privacy decisions after financial decisions reduces their aversion to privacy risk. Finally, surveyed attitude to privacy and explicit willingness to pay or to accept payment for personal information correlate well with willingness to incur privacy risk. Having shown that privacy loss can be assimilated to a monetary loss, we compare decisions to incur risk in privacy lotteries with risk attitude in monetary lotteries to derive estimates of the implicit monetary value of privacy. The average implicit monetary value of privacy is about equal to the average willingness to pay to protect private information, but the two measures do not correlate at the individual level. We conclude by underlining the need to know individual attitudes to risk to properly evaluate individual attitudes to privacy as such.
Keywords: C91; D81; O30; 330; privacy; disclosure; risk; control; personal information; experiment